Determination of Soil Barrier Resistance Influence to Compact Nuclear Power Plant at Emergency Situation - O. A. Gubeladze; A. R. Gubeladze (Глобальная ядерная безопасность, 2022)
The article discusses the development of an emergency situation in which a compact nuclear power plant, under the influence of the conventional explosive detonation products, moves to a ground barrier. A model that makes it possible to determine the obstacle resistance force for various initial object-soil interaction velocities is presented.